Productivity of a preparative high‐performance liquid chromatography isolation of anacardic acids from cashew nut shell liquid. Issue 6 (29th April 2019) - Oiram Filho, Francisco; Zocolo, Guilherme J.; Canuto, Kirley M.; Silva Junior, Ivanildo J. da; de Brito, Edy S.
Abstract: The anacardic acids are alkyl phenols, with biological activities, obtained as a byproduct from cashew nut processing. The anacardic acids isolation by preparative reversed phase high‐performance liquid chromatography was developed injecting large pulse from 50 to 200 mg of cashew nut shell liquid through a C18 column eluted with methanol, water and acetic acid (80:20:1). The separations were carried out at 25°C and monitored at 280 nm. Yield, recovery, purity, solvent consumption and productivity were analyzed. The results of anacardic acids isolation pointed the concentration loading of 100 mg as a process threshold leading to a productivity of 0.681 Kg.day −1 .Kg −1 of anacardic acids with purity of 96.41, 95.32 and 90.77% for anacardic acid triene, diene and monoene, respectively.